Peritumoral tissue compression is predictive of exudate flux in a rat model of cerebral tumor: an MRI study in an embedded tumor. (1st October 2015) - Ewing, James R.; Nagaraja, Tavarekere N.; Aryal, Madhava P.; Keenan, Kelly A.; Elmghirbi, Rasha; Bagher‐Ebadian, Hassan; Panda, Swayamprava; Lu, Mei; Mikkelsen, Tom; Cabral, Glauber; Brown, Stephen L.
<x xml:space="preserve">Abstract</x> MRI estimates of extracellular volume and tumor exudate flux in peritumoral tissue are demonstrated in an experimental model of cerebral tumor. Peritumoral extracellular volume predicted the tumor exudate flux. Eighteen RNU athymic rats were inoculated intracerebrally with U251MG tumor cells and studied with dynamic contrast enhanced MRI (DCE‐MRI) approximately 18 days post implantation. Using a model selection paradigm and a novel application of Patlak and Logan plots to DCE‐MRI data, the distribution volume (i.e. tissue porosity) in the leaky rim of the tumor and that in the tissue external to the rim (the outer rim) were estimated, as was the tumor exudate flow from the inner rim of the tumor through the outer rim. Distribution volume in the outer rim was approximately half that of the inner adjacent region (p < 1 × 10−4). The distribution volume of the outer ring was significantly correlated (R2 = 0.9) with tumor exudate flow from the inner rim. Thus, peritumoral extracellular volume predicted the rate of tumor exudate flux. One explanation for these data is that perfusion, i.e. the delivery of blood to the tumor, was regulated by the compression of the mostly normal tissue of the tumor rim, and that the tumor exudate flow was limited by tumor perfusion. Copyright © 2015 John Wiley & Sons, Ltd.